Female doping: observations from a data lake study in the Hospital District of Helsinki and Uusimaa, Finland - Paula Katriina Vauhkonen; Teemu Daniel Laajala; Katarina Mercedes Lindroos; Mikko Ilari Mäyränpää (BMC Women's Health, 2023)
Abstract Background Doping is a well-recognized risk factor for several potentially severe health effects. Scientific literature concerning the need for medical treatment for such adversities is still sparse. This is especially true for women, due to lower doping use prevalence compared to men. Our study explored the nature of medical contacts and deviance in red blood cell parameters of female patients with doping use in Finnish specialized health care. Methods This was a retrospective register study. The study sample was gathered from the Hospital District of Helsinki and Uusimaa, Finland (HUS) Datalake. An exhaustive search for doping related terms was performed to find patients with doping use documentation within free-text patient records. Medical record data was supplemented with laboratory data and medical diagnoses covering a total observation time of two decades. Statistical analysis included Fisher's Exact Test and one-way ANOVA. Results We found 39 female patients with history of doping use and specialized health care contacts in the HUS-area between 2002–2020. At initial contact (i.e., the first documentation of doping use), the mean age of these patients was 33.6 years (min 18.1, max 63.5, SD 10.6). The most frequently used doping agents were anabolic androgenic steroids (AAS). The initial contacts were significantly more often acute in nature among patients with active doping use than among patients with only previous use (no use within one year; p = 0.002). Psychiatric and substance use disorder (SUD) morbidity was high (46.2% and 30.8%, respectively). Eight patients (20.5%) had received specialized health care for acute poisoning with alcohol or drugs, and nine (23.1%) for bacterial skin infections. Less than 45% of patients with active AAS use presented with off-range red blood cell parameters. Conclusions Our findings suggest that female patients with a history of doping use encountered in specialized health care may exhibit high psychiatric and SUD related morbidity. Also, majority of patients with AAS use had red blood cell parameters within-range. Further studies are required to assess the generalizability of these findings to patients within primary health care services, and to determine the usefulness of hematological parameters as indicators of AAS use in female patients.